Response of human subjects using different biodynamic CAD models. (2020) - Kumar, Rohit; Singh, Ishbir; Kalsi, Sachin
Abstract: Human subject suffers from many problems when it comes into contact with conditions of vibrations while travelling, working etc. in sitting posture. This result into a headache, body ache, increase in heart rate etc., therefore it becomes necessary to study the Whole body vibrations effect on human subject. Taking this into investigation, a current study has been conducted to discover the vibration effect on human subject using three different CAD models i.e. 54 kg ellipsoidal model, 76 kg solid model (single layer) and 76 kg 3-layer CAD model. All these CAD models have been modelled using 50th percentile for 54 kg and 95th percentile for 76 kg anthropometric data of Indian male population with reference from existing literature. The boundary conditions have been considered as per real conditions for different vibration conditions in sitting posture. Current study has been conducted to evaluate the mode shapes corresponding to natural frequency of each CAD model to observe the response of human subject in WBV. The comparisons of results obtained from all these CAD models have been done and it's found that maximum deformation is obtained in head. It has been observed from the results that with a rise in natural frequency of any of the biodynamic CAD model, deformation also gets increase and also, 3-layer model found to be best model for studying the effect of WBV on human subject. The results of all CAD models have been compared and validated with the existing literature.